Prevalence and Classification of C-Shaped Canal and Radix in Mandibular Molars Using Cone-Beam Computed Tomography on Mexican Population - Hugo Bojorquez Armenta; Angel Gustavo Romo Mireles; Javier Solis Martinez; Jesus Pescador Alvarez; Yarely Ramos Herrera; Omar Tremillo Maldonado; Oscar Almeda Ojeda; Jose Salas Pacheco; Gamaliel Ortiz Sarabia; Francisco Xavier Castellanos-Juarez; Sergio Salas Pacheco (MDPI AG, 2024)
The diverse morphological configurations in teeth present clinical challenges in root canal treatment, complicating instrumentation and irrigation processes, which can lead to treatment failure. Understanding anatomical variations, such as C-shaped canals and radix entomolaris, enhances clinical skills and improves long-term endodontic treatment success rates. Cone-beam computed tomography (CBCT) offers superior diagnostic capabilities over conventional radiography, enabling the pre-operative detection of root configurations and canal numbers, facilitating personalized endodontic treatments. A total of 2173 teeth of a Mexican population, including 1057 first mandibular molars and 1116 s mandibular molars, were studied using only CBCT to identify C-shaped canals and radix configurations of patients who were treated from 2018 to 2023 at the Department of Radiology at the Faculty of Dentistry, Juarez University of the State of Durango, Mexico. C-shaped canals were identified in 160 teeth, with a prevalence of 0.2% in first mandibular molars and 14.1% in second mandibular molars. The highest frequency was in the left second mandibular molar (3.7) at 14.8%. Gender differences were significant, with higher prevalence in females (27.3%) compared to males (13.3%). The most common C-shaped canal configuration was type C2 (39.3%). Radix entomolaris was found in 52 teeth, with a prevalence of 3.4% in first mandibular molars and 1.4% in second mandibular molars. This research on a Mexican population using cone-beam computed tomography (CBCT) highlights significant findings in the prevalence and types of C-shaped canals and radix entomolaris in mandibular molars for this population. The left second mandibular molar (3.7) showed the highest prevalence at 14.8%, followed closely by the right second mandibular molar (4.7) at 13.5%, with a significant difference (p < 0.001). We found a significant difference in the prevalence of C-shaped canals between genders (p = 0.004, OR 1.78). Additionally, radix entomolaris (p < 0.001) was more frequently identified in first mandibular molars to a significant degree. These insights underscore the importance of CBCT in diagnosing complex root anatomies, which can greatly enhance the success rates of endodontic procedures by allowing for more tailored and precise treatments for this population.